2015
DOI: 10.4103/0028-3886.156274
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of neurologists and neurosurgeons in India and its relevance to the adoption of telemedicine

Abstract: Majority of Indians have no access to centres of neurological excellence in the country. A detailed analysis of 3666 members of the Neurological Society of India and the Indian Academy of Neurology revealed that not a single member lived in a geographical area covering 934.8 million people. 30.09% live in the four major metropolitan cities, 29.54% in the state capitals, 30.58% in Tier 2 cities, 7.12% in tier 3 cities and 2.67% in rural areas covering a population of 84.59 million. Building additional neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 36 publications
0
35
0
4
Order By: Relevance
“…5,6 Scarcity of neurosurgeons get compounded by the fact that more than 80% of India's specialist doctors live in urban India. 7 A study by Neurological Society of India found that there was not a single neurosciences specialist living in a geographical area covering nearly 934.88 million people. 7 Therefore, patients of neurotrauma often have to travel hundreds of kilometers to have an expert opinion and management thereof; needless to say, golden hour of trauma is surely lost in this time.…”
Section: Neurosurgeon: a Scarce Resourcementioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Scarcity of neurosurgeons get compounded by the fact that more than 80% of India's specialist doctors live in urban India. 7 A study by Neurological Society of India found that there was not a single neurosciences specialist living in a geographical area covering nearly 934.88 million people. 7 Therefore, patients of neurotrauma often have to travel hundreds of kilometers to have an expert opinion and management thereof; needless to say, golden hour of trauma is surely lost in this time.…”
Section: Neurosurgeon: a Scarce Resourcementioning
confidence: 99%
“…7 A study by Neurological Society of India found that there was not a single neurosciences specialist living in a geographical area covering nearly 934.88 million people. 7 Therefore, patients of neurotrauma often have to travel hundreds of kilometers to have an expert opinion and management thereof; needless to say, golden hour of trauma is surely lost in this time. 7 Scarcity of neurosurgeons is not limited to developing world; it is a problem in developed world too.…”
Section: Neurosurgeon: a Scarce Resourcementioning
confidence: 99%
See 1 more Smart Citation
“…Other determinants that have an impact on the adoption of telehealth in India and Pakistan include accessibility to healthcare professionals, the quality and reliability of the ICT infrastructure within a region, the shortage of healthcare professionals in rural and remote locations, patient education regarding the benefits of telehealth, patient demographics and technology safety and awareness [3,[26][27][28][29][30][31]21,[42][43][44]32,45,46]. This research focuses on one specific determinant, the quality of images transmitted within the telehealth environment in India and Pakistan, as it is evident, from a review of the literature that scant studies have been undertaken on this topic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role of ICT in the field of neurology, especially in stroke care and management of epilepsy has been recently emphasized in several studies [36][37][38][39]. Presently, there is a severe shortage of trained neurologists and stroke care specialists, particular in the rural areas in India [36].…”
Section: Involvement Of Private Enterprise In the Field Of Telemedicimentioning
confidence: 99%